(3CQV GdWhWe (B/s - (3GdRjfj, CSGeI YHO GdefYe,s 1971- ((3dfOf (B:s (3OGQ GdeMJSH ddfTQ hGdJhRjY (B:s (3OGQ QhGjI,s, 2010)
(3QhGjI CQV GdWhWe ddcGJH CSGeI GdRjfj UOQJ Yf OGQ GdeMJSH(B.. (3hjbhd GdeDda aj LRA ef GdQhGjI (B: (3fYe de Jcf eDSSJce eDSSI NjQjI CHOG hde jcf eSLOce ddJbhi(B.. (3Cfi ddJbhd Ef JLO SHjdG Edi bUQ GdCaGYj hGdKYGHjf GdPj JScfhfg(B.. (3bUQ GdWhWe (B((3fYeGf fGaY(B) (3GdCNWHhW GdPj da RhGFOg GdOhOjI GdgGFdI Ydi cd TjA aj GdeOjfI da HgG CYfGbfG GdeTOhOI Edi ecJHg GdaGQg CYdi fGWMI GdSMGH(B. (3QhGjI CQV GdWhWe LGAJ aj (B216 (3UaMI ef GdMLe GdUZjQ(B.. (3hGdeDda CSGeI GdRjfj MGR YOOG ef GdLhGFR GdYQHjI Yf CYeGdg GdCOHjI(B.s
Keywords: (3GdbUU GdYQHjIs -- (3eUQs -- (3bQf (B21s; (3GdCOH GdYQHjs -- (3eUQs -- (3bQf (B21s